Change in the ductility characteristics of austenitic steels during deformation at different rates - Shinkarenko, E.T. (Проблемы прочности, 1985)
The present study investigates the ductility of stable austenitic steels 07KhI3AGI9N5 and 12KhI8N22T and metastable austenitic steel 03KhI3AGI9.